Effect of nitrogen and phosphorus levels on growth and grain yield of maize (Zea mays L.), Gezira State, Sudan - Mohamed, Ibrahim; Kareem, Hussam; Gangi, Ali .; Daffalla, Ahmed (Gezira Journal of Agricultural Science; Vol 17 No 1 (2019), 2019)
Maize ( Zea mays L.)  is an annual, cross-pollinated warm weather crop. It is the world's third leading cereal crop after wheat and rice. Recently, maize gained more importance as a forage and food crop in the Sudan. The objective of this study was to determine the optimum level of nitrogen and phosphorus to maximize grain yield of maize. This study was conducted at the Experimental Farm, Faculty of Agricultural Sciences, University of Gezira, during the summer of 2017 and winter season of 2017/18. A randomized complete block design with four replicates was used. Four nitrogen levels, namely, 0, 43, 86 and 129 kg N/ha and two phosphorus levels, 0 and 43 P 2 O 5 kg/ha were used. Results showed that nitrogen significantly increased plant height, leaf area index, days to 80% tasseling, number of grains/ear and grain yield in both seasons. Nitrogen levels had a significant effect on days to 80% silking in the winter season only. Phosphorus had no significant effect on most of the parameters measured in this study. The interaction between nitrogen and phosphorus levels had a significant effect on plant height, days to 80% silking, number of grains/ear and 100 - grain weight in the winter season only. The results revealed that the interaction between N and P levels had a significant effect on grain yield in both seasons. The highest grain yield (3825 and 4401 kg/ha) was obtained by the application of 129 and 86 kg N/ha in the summer and winter seasons, respectively. To obtain high grain yield of maize, it is recommended to apply 129 and 86 kg N / ha in the summer and winter seasons, respectively, without phosphorus application.   الذرة الشامية محصول حولي، خلطي التلقيح ومن محاصيل الجو الدافئ. الذرة الشامية ثالث أهم محاصيل الحبوب في العالم بعد القمح والأرز. حديثاً اكتسب الذرة الشامية أهمية كبيرة كمحصول غذاء وعلف في السودان. تهدف هذه الدراسة لتحديد تأثير مستويات النتروجين والفسفور على نمو وإنتاجية حبوب الذرة الشامية. نفذت الدراسة في المزرعة التجريبية كلية العلوم الزراعية, جامعة الجزيرة، وادمدني، السودان خلال موسمي صيف 2017 وشتاء 2017/18. تم استخدام نظام القطاعات العشوائية الكاملة بأربع مكررات. اشتمل النتروجين على 4 معاملات (0, 43, 86, 129 كجم نتروجين/هكتار) والفسفور معاملتان (0, 43 كجم خامس أكسيد الفسفور/هكتار). أظهرت النتائج أن إضافة النتروجين أدت إلى زيادة معنوية في طول النبات ودليل مساحة الورقة وعدد الايام 80% زهرة مذكرة وعدد الحبوب في الكوز وانتاجية الحبوب في الموسمين. كما أن إضافة النتروجين كان لها تأثيراً معنوياً على عدد الايام 80% زهرة مؤنثة  خلال الموسم الشتوي فقط. لم يكن لإضافة الفسفور أي تأثير معنوي علي معظم المؤشرات التي تمت دراستها. التداخل بين مستويات النتروجين والفسفور كان لها  تأثيراً معنوياً على طول النبات وعدد الايام   80% زهرة مؤنثة وعدد الحبوب في الكوز ووزن 100 حبة في فصل الشتاء فقط. أظهرت النتائج أن التداخل بين مستويات النتروجين والفسفور كان له تأثيراً معنوياً على إنتاجية الحبوب خلال الموسمين، أعلى انتاجية (3825 و 4401 كجم/هكتار) تحققت عند إضافة 129 و 86 كجم/هكتار  في الصيف والشتاء على التوالي. لتحقيق إنتاجية عالية من حبوب الذرة الشامية توصى الدراسة بإضافة 129 و 86 كجم نتروجين/هكتار في موسمي الصيف والشتاء على التوالي بدون إضافة الفسفور.